Python for secret agents : analyze, encrypt, and uncover intelligence data using python, the essential tool for all aspiring secret agents - Lott, Steven F. (Community experience distilled., 2014)
If you are a Python beginner who is looking to learn the language through interesting projects, this book is for you. A basic knowledge of programming and statistics is beneficial to get the most out of the book.